2020
DOI: 10.1371/journal.pone.0241570
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of adult heart, lung, and heart-lung transplantation recipients: A systematic review of qualitative research evidence

Abstract: Aim To review evidence about the experience of being the recipient of a donated heart, lungs, or heart and lungs. Design A systematic review (registered with PROSPERO: CRD42017067218), in accordance with PRISMA guidelines. Data sources Seven databases and Google Scholar were searched in May 2017 and July 2019 for papers reporting English-language research that had used qualitative methods to investigate experiences of adult recipients. Review methods Quality was assessed and results were analysed themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
(234 reference statements)
1
13
0
Order By: Relevance
“…The participants clearly stated that they hope to live longer and enjoy a higher quality of life. These findings are consistent with the results of a qualitative systematic review of the experiences of heart, lung, and heart-lung transplant recipients, which found that patients regard transplantation as a chance to lead a life with a much better state of health (Stubber & Kirkman, 2020). The testimonies recorded in that study recall those indicated by our patients, with expressions such as "second chance", "back to normality" and "resumption of life".…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The participants clearly stated that they hope to live longer and enjoy a higher quality of life. These findings are consistent with the results of a qualitative systematic review of the experiences of heart, lung, and heart-lung transplant recipients, which found that patients regard transplantation as a chance to lead a life with a much better state of health (Stubber & Kirkman, 2020). The testimonies recorded in that study recall those indicated by our patients, with expressions such as "second chance", "back to normality" and "resumption of life".…”
Section: Discussionsupporting
confidence: 90%
“…Patients on the waiting list also experience fear, as reported by a recent qualitative systematic review (Stubber & Kirkman, 2020) of the experiences of recipients of heart, lung, and heart-lung transplants. Those authors noted that their patients frequently reported feeling afraid both of the transplant and its implications and also of the disease itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps we observed uniquely elevated PTG because, unlike our other assessments of positive outcomes, it pertained directly to the transplant and captures sentiments reported in qualitative studies regarding how profoundly the transplant experience can emotionally affect recipients. 95 Our sample's high PTG may also reflect the fact that we assessed it later post-transplant compared to other studies.…”
mentioning
confidence: 85%